Altmetria ou métricas alternativas: conceitos e principais características - Iara Vidal Pereira de Souza (AtoZ: Novas Práticas em Informação e Conhecimento, 2015)
This interview presents the concepts and characteristics of the alternative metrics (or altmetria, in portuguese), emphasising their relationship to the traditional metrics and the potential for hazards, mainly artificial data manipulation. Discusses the challenges for such metrics and the tools available.